2014
DOI: 10.4014/jmb.1309.09029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diet in Shaping Gut Microbiota Revealed by a Comparative Study in Infants During the Six Months of Life

Abstract: The development of the gut is controlled and modulated by different interacting mechanisms, such as genetic endowment, intrinsic biological regulatory functions, environment influences and last but no least, the diet influence. In this work, we compared the fecal microbiota of breast-fed (BF), formula-fed (FF), and mixed-fed (MF) infants from Hebei Province, China. By using high-throughput 16S rDNA sequencing analyses, we found some differences in gut microbiota in the three groups. Firmicutes and Proteobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 36 publications
(61 reference statements)
4
42
1
1
Order By: Relevance
“…34,35 Fiber intake has been previously attributed beneficial health properties by the virtue of being a substrate for short-chain fatty acids (SCFA) production. 36,37 The lack of association between microbiota and fiber intake despite the 5-fold difference between the low and high fiber intake quartiles (6 ± 3 vs 34 ± 16 g/d) was likely the relatively modest fiber intake because 50 g/d fiber had been recommended for patients with diabetes. 38 In addition, soluble and fermented fiber more than nonfermented fiber was likely the source for SCFA, and a recent meta-analysis suggested that cereal but not fruit fiber as well as a lower BMI might be protective against diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Fiber intake has been previously attributed beneficial health properties by the virtue of being a substrate for short-chain fatty acids (SCFA) production. 36,37 The lack of association between microbiota and fiber intake despite the 5-fold difference between the low and high fiber intake quartiles (6 ± 3 vs 34 ± 16 g/d) was likely the relatively modest fiber intake because 50 g/d fiber had been recommended for patients with diabetes. 38 In addition, soluble and fermented fiber more than nonfermented fiber was likely the source for SCFA, and a recent meta-analysis suggested that cereal but not fruit fiber as well as a lower BMI might be protective against diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…While it is conventionally considered beneficial to have greater gut microbiome diversity, this diversity is untested in regards to its effects on CNS functions, and may not be universally beneficial. The authors cite studies by Fan et al and Roger et al which show increases in microbiome diversity in CNS altered populations such as autism, alluding to a potentially negative impact of increased microbiome diversity [39,40].…”
Section: Human Studiesmentioning
confidence: 99%
“…Just as delivery mode can affect the neonatal microbiota, so can the infant's early diet, with differences in breast vs formula-fed infants observed (12). Although such studies were by necessity observational, large differences were also observed in macaques assigned to formula- vs breast-fed diets (13).…”
Section: Development Of the Microbiomementioning
confidence: 99%